A Study of School Students’ Knowledge about Climate Change Science in India - Shimray, Chong; Shirol, Shrishail E (SCHOOL SCIENCE, 2020)
This paper can be considered a preliminary study to have an idea about the implementation of climate change education in India. An attempt was made to assess school students’ knowledge about climate change science based on ten closed statements, some of which were part of the curriculum in some way, while the rest of the statements were related to important climate change science concepts. A comparison was also made to determine if students who have manifested interest in science have more knowledge about climate change science than the rest. The findings of the study are expected to be useful for curriculum developers and other stakeholders of school education in India to prepare a robust curriculum on climate change